Odpowiedź :
Hej!
[tex](\frac{3}{4})^5\cdot(1\frac{1}{3})^5=(\frac{3}{4}\cdot\frac{4}{3})^5=1^5=\boxed1\\\\(-8)^4\cdot(\frac{1}{4})^4=(-8\cdot\frac{1}{4})^4=(-2)^4=\boxed{16}\\\\(0,7)^2\cdot(-10)^2=(0,7\cdot(-10))^2=(-7)^2=\boxed{49}\\\\(\frac{2}{3})^3\cdot(-6)^3\cdot(1\frac{1}{2})^3=(\frac{2}{3}\cdot(-6)\cdot\frac{3}{2})^3=(-6)^3=\boxed{-216}[/tex]
Pozdrawiam! - Julka
Cześć!
Odpowiedź:
Szczegółowe wyjaśnienie:
a)
[tex](\frac{3}{4} )^{5} \cdot(1\frac{1}{3} )^{5} =(\frac{3}{4}\cdot1\frac{1}{3} )^{5} =(\frac{3}{4} \cdot\frac{4}{3})^{5} =1^{5}=1[/tex]
b)
[tex](-8)^{4} \cdot(\frac{1}{4} )^{4} =8^{4}\cdot(\frac{1}{4}) ^{4}=(8\cdot\frac{1}{4})^{4} =2^{4} =16[/tex]
c)
[tex](0,7)^{2} \cdot(-10)^{2}=(0,7\cdot(-10))^{2} =(-7)² =49[/tex]
d)
[tex](\frac{2}{3} )^{3} \cdot(-6)^{3} \cdot(1\frac{1}{2}) ^{3} = \\(\frac{2}{3} )^{3} \cdot(-6)^{3} \cdot(1\frac{1}{2}) ^{3} =\\ -(\frac{2}{3}\cdot6\cdot1\frac{1}{2} )^{3} =-(\frac{2}{3}\cdot6\cdot\frac{3}{2} )^{3} =-6^{3}[/tex]
Pozdrawiam,
MrBarte!